Breast cancer diagnosis in a resource poor environment through a collaborative multidisciplinary approach: the Kenyan experience. Issue 4 (1st February 2013) - Sayed, Shahin; Moloo, Zahir; Bird, Peter; Wasike, Ronald; Njoroge, Wambui; Karanu, Joseph; Nzioka, Ancent; Sherman, Omar; Prasad, Satya; Mariwa, Costa; Otieno, James Obondi; Chumba, David; et al.
Abstract : INTRODUCTION: The majority of women with breast cancer in Kenya present with node-positive (stage II) or locally advanced Q7 disease (stage IIIB). Diagnosis is made on fine needle aspirate cytology and treatment is with surgery if resectable. Diagnostic core biopsy is available only at subspecialty hospitals. Processing and reporting of biopsy tissue are not standardised. Hormone receptor and HER2 analyses are rarely done preoperatively. METHODS: As part of a larger study investigating the prevalence of triple negative breast cancer in Kenya, a multidisciplinary workshop of collaborators from 10 healthcare facilities was held. Process gaps were identified, preanalytic variables impacting on ER/PR/HER2 discussed and training in core biopsy provided. Local remedial strategies were deliberated. CONCLUSION: We describe our experience and outcome from the workshop, which can be modelled for other resource poor settings.